New Directions for Evaluation - John S. Risley (The Evaluation Center at Western Michigan University, 2005)
The two most recent issues of New Directions for Evaluation each cover international perspectives in the field. The Fall 2004 issue (Rugg, Peersman, and Carael) addressed "Global Advances in HIV/AIDS Monitoring and Evaluation" while the Winter 2004 issue (Russon and Russon) concerned "International Perspectives on Evaluation Standards."